Comparative analysis of mite genomes reveals positive selection for diet adaptation - Qiong Liu; Yuhua Deng; An Song; Yifan Xiang; De Chen; Lai Wei (Communications Biology, 2021)
Liu et al. present a comparative analysis of 15 genomes from mites and identify genetic signatures for diet specialisation. Different gene families and selective pressures were revealed for herbivorous, haematophagous and fat-feeding species.